Răspuns :
Răspuns:
a) (x-8)(x-3)
b) (x-7)(x-5)
c) ((x-6)(x-2)
d) (x-2)(x-1)
e) (x-8)(x-1)
f) (x-10)(x-4)
Explicație pas cu pas:
x²-11x+24=x²-8x-3x+24=x(x-8)-3(x-8)=(x-3)(x-8)
x²-12x+35=x²-7x-5x+35=x(x-7)-5(x-7)=(x-7)(x-5)
x²-8x+12=x²-2x-6x+12=x(x-2)-6(x-2)=(x-6)(x-2)
x²-3x+2=x²-x-2x+2=x(x-1)-2(x-1)=(x-2)(x-1)
x²-9x+8=x²-x-8x+8=x(x-1)-8(x-1)=(x-8)(x-1)
x²-14x+40=x²-10x-4x+40=x(x-10)-4(x-10)=(x-4)(x-10)
x²-20x+36=x²-18x-2x+36=x(x-18)-2(x-18)=(x-18)(x-2)
x²-20x+75=x²-5x-15x+75=x(x-5)-15(x-5)=(x-15)(x-5)
x²-13x+40=x²-8x-5x+40=x(x-8)-5(x-8)=(x-8)(x-5)
KAWAIIMATH